Calculate Some Special Function For The Design of Cavity Linear Accelerator - Nassrullah, D. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The purpose of this project is to build a scientific base and computational programs in an accelerator design work. The transfer of group of laws in alinear accelerator cavity to computer codes written in Fortran power station language is inorder to get a numerical calculation of an electromagnetic field generated in the cavities of the linear accelerator. The program in put contains mainly the following, the geometrical cavity constant, and the triangular finite element method high – order polynomial. The out put contains vertical and horizontal components of the electrical field together with the electrical and the magnetic field intensity.